ANALISIS PENGGUNAAN MEDIA KONKRET UNTUK MENINGKATKAN MINAT BELAJAR IPAS SISWA KELAS V SD N JARAKAN PANGGUNGHARJO SEWON BANTUL YOGYAKARTA - Etza Sabilillah; Hermawan Wahyu Setiadi (STKIP Subang, 2026)
The use of concrete media in science education is one of the efforts to help students understand concepts through direct experience. The use of concrete media in learning has been carried out optimally and has played a role in increasing students' interest in learning, as seen from the increased attention, involvement, and interest of students during the learning process. This study aims to: 1) describe the process of using concrete media in science learning; and 2) analyze the impact of using concrete media on increasing the interest of fifth-grade students at Jarakan Public Elementary School in learning. This study used a qualitative method with a phenomenological approach. Data were collected through interviews, observations, and documentation of teachers and fifth-grade students at Jarakan State Elementary School. Data analysis used the Miles and Huberman model through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that: 1) the use of concrete media was carried out in a planned manner and was adapted to the learning material. Concrete media helped students understand concepts more clearly through direct observation. Teachers also adjusted their strategies to overcome the limitations of media and learning time; and 2) the use of concrete media had a positive impact on students' interest in learning, as shown by increased attention, activity, and interest among students in participating in learning. Keywords: Concrete Media, IPAS Learning, Learning Interest, Qualitative Method